Phenotypic patterns of antimicrobial resistance in Campylobacter spp. in Ukraine - N. V. Shchur; D. O. Stepanskyi; S. V. Shuliak; L. V. Balanchuk; V. V. Skliar; L. M. Moskalenko; T. M. Ponomarova-Herasymiuk; M. V. Lusta; V. V. Nedosekov (Regulatory Mechanisms in Biosystems, 2024)
Campylobacter spp. are major foodborne zoonotic pathogens that have recently become more resistant to fluoroquinolones and macrolides, which are broad-spectrum antibiotics used in both medicine and veterinary practice. Campylobacter is a commensal of the intestines of mammals and birds, which facilitates the transfer of antimicrobial resistance (AMR) determinants from other bacteria through horizontal gene transfer. The aim of this study was to establish the prevalence and determine the AMR phenotypes of Campylobacter species isolated in Ukraine. Using the disk diffusion method (DDM), 33 isolates of Campylobacter spp. isolated from animals and poultry on farms between May and September 2023 were tested. Additionally, an analysis of the resistance of 293 Campylobacter spp. isolates obtained from children with acute intestinal infections from 2020 to 2023 was conducted. The level of resistance of clinical Campylobacter spp. to ciprofloxacin (CIP) was found to be 83.3%, to tetracycline (TE) 53.6%, to erythromycin (E) 11.6%, and the isolates from farms showed resistance to ciprofloxacin (CIP) at 72.7%, to tetracycline (TE) at 60.6%, and to erythromycin (E) at 18.2%. In 4.1% of clinical isolates, multidrug resistance (MDR) (CIP/TE/E) was detected, with the most common AMR combination being (CIP/TE), reaching 42.7%. Resistance to at least one antibiotic was found in 37.8%. The isolates from animals and poultry had a multiple antibiotic resistance rate of 12.1%, with 42.4% being resistant to at least one antibiotic. This study provides insight into the relevance and importance of Campylobacter spp. resistance in Ukraine. It expands the understanding of the issue, which requires more detailed study, including the molecular mechanisms of resistance and the identification of genetic determinants shaping the epidemiology of antimicrobial resistance in Ukraine. For this purpose, a collection of isolates has been created, and optimal long-term storage conditions have been selected, which will allow the study of Campylobacter spp. decades from now.